MENTORING PENYUSUNAN VISI, MISI, DAN NILAI BEKASI KEREN - Zahara Tussoleha Rony; Sani Aryanto; Dwi Setyowati (Bajang Institute, 2022)
Bekasi Keren is a non-profit organization that is developing and preparing to become a profit and independent organization seeking to review the vision and mission as well as organizational values ​​which are important elements in an organization. Therefore, the purpose of community service is to help Bekasi Keren have a solid vision, mission and values ​​that have an impact on increasing productivity. The method of increasing community service competence is carried out by means of brainstorming, workshops, mentoring accompanied by informal coaching. This community service is expected not only to produce a vision and mission as well as values ​​that are in accordance with the needs of the organization but to be able to foster commitment and foster the work spirit of Bekasi Keren members which has an impact on the breadth of benefits for the people of Bekasi and its surroundings.